Two new species of Torymidae (Hymenoptera: Chalcidoidea) reared from flower heads of Echinops orientalis Trautvetter in south-eastern Turkey. Issue 3 (3rd July 2018) - Doğanlar, Mikdat; Aslan, M. Murat
Abstract : Two new species of torymids, Pseudotorymus hasanberkayi sp. n. and Microdontomerus kahramanmarasensis sp. n. (Hymenoptera: Torymidae), were reared from flower heads of Echinops orientalis Trautvetter (Asteraceae) collected in Kahramanmaraş province, south-eastern Turkey. The new species are described and their diagnostic characters are illustrated. http://www.zoobank.org/urn:lsid:zoobank.org:pub:848B4E9D-AE8A-4EF8-8072-1F28BE21ADA1